51 Contact Force Data Availability Reduces Acute Pulmonary Vein Reconnection: Early Results from the Smart AF Trial. (6th June 2015) - Ullah, Waqas; McLean, Ailsa; Tayebjee, Muzahir; Gupta, Dhiraj; Ginks, Matthew; Haywood, Guy; O'Neill, Mark; Lambiase, Pier; Earley, Mark; Schilling, Richard; Smart, AF
Abstract : Introduction: Contact force (CF) sensing data may facilitate wide area circumferential ablation (WACA). We present data from an interim analysis of the first multicentre randomised controlled trial studying the impact of this data on the ablation of paroxysmal atrial fibrillation (PAF). Methods: At 7 UK centres, patients undergoing first-time PAF ablation were randomised to ablation with (CF-on) or without CF data (CF-off) available to the operator. Planned recruitment is 120 patients with 1 year follow-up. Using a 3D mapping system and the SmartTouch CF-sensing catheter (Biosense Webster), all patients underwent WACA. Subsequently a 1 h waiting time was observed before assessing acute pulmonary vein (PV) reconnection; if the PV remained isolated, 18 mg adenosine was administered intravenously. The primary end point was acute PV reconnection (spontaneous/adenosine induced). PVs were assessed separately, but cases of a common trunk were taken as one vein. PVs that appeared isolated but were assessed without completing the waiting period were excluded from the acute reconnection analysis. Follow-up is ongoing and 3 month outcomes are reported. Results: 116 patients have been recruited: age 59 ± 11 years, 57% male, EHRA score 2.7 ± 0.6, AF duration 37 [16–70] months (no significant baseline characteristic differences between groups). There were no differences in procedural parameters (Table 1). There was a significant, 40%, reduction in acute PV reconnection in the CF-on group (Table 1). There were two tamponades and one minor pericardial effusion in the CF-on group, and 1 minor haematoma in the CF-off group. 90 patients (43 CF-off, 47 CF-on) have completed 3 month follow-up: at this point there is no difference in EHRA scores (CF-off 1.6 ± 0.6, CF-on 1.5 ± 0.6, p = 0.8). Conclusions: Addition of CF sensing data had no impact on procedure, fluoroscopy or ablation times, but did reduce acute PV reconnection rates, suggesting more effective ablation application, and consequently more durable PV isolation. Whether this translates to improved long-term success will be assessed on study completion.